UV Filters: Challenges and Prospects - Jesus, Ana (2022)
The use of sunscreens is an established and recommended practice to protect skin from solar-induced damage. Around 30 UV filters can be used in sunscreen products in the European Union, which ought to follow the requirements of the regulation 1223/2009 to ensure their efficacy and safety for humans. Nevertheless, low photostability and putative toxicity for humans and environment have been reported for some UV filters. Particularly, the negative impact in marine organisms has recently raised concern on the scientific community. Therefore, it is important to develop new UV filters with improved safety profile and photostability. Over the last two decades, nearly 200 new compounds have revealed promising photoprotection properties. The explored compounds were obtained through different approaches, including exploration of natural sources, synthetic pathways, and nanotechnology. Almost 50 natural products and around 140 synthetic derivatives, such as benzimidazoles, benzotriazoles, hydroxycinnamic acids, xanthones, triazines, among others, have been studied aiming the discovery of novel, effective, and safer future photoprotective agents. Herein, we provide the reader with an overview about UV filters' challenges and prospects, offering a forward-looking to the next-generation of UV filters.